Two new keratinophilic fungal species - Zhang, Yan-Wei; Zeng, Gui-Ping; Zou, Xiao; Han, Yan-Feng; Liang, Zong-Qi; Qiu, Shu-Yi (Phytotaxa, 2017)
Two new keratinophilic fungal species, Chrysosporium jingzhouense and C. clavisporum, were isolated from farmland soil of Jingzhou City, Hubei Province, and from plant root soil of Guigang City, Guangxi Province, China, respectively, using child hair as bait. Molecular and morphological characters were used to identify taxonomic status. The phylogeny shows C. jingzhouense is clustered with C. articulatum and C. keratinophilum; while C. clavisporum appears to be related to C. qinghaiense, C. indicum and C. linfenense. These previously described Chrysosporium species can be easily distinguished from our proposed new species based on morphology alone. The holotypes, ex-types and ex-isotypes have been deposited in the Institute of Fungus Resources (GZAC).